2010
DOI: 10.1103/physrevlett.104.195001
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Mode-Coupling Instability in Two-Dimensional Plasma Crystals

Abstract: Dedicated experiments on melting of 2D plasma crystals were carried out. The melting was always accompanied by spontaneous growth of the particle kinetic energy, suggesting a universal plasma-driven mechanism underlying the process. By measuring three principal dust-lattice (DL) wave modes simultaneously, it is unambiguously demonstrated that the melting occurs due to the resonance coupling between two of the DL modes. The variation of the wave modes with the experimental conditions, including the emergence of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
146
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(161 citation statements)
references
References 35 publications
15
146
0
Order By: Relevance
“…Using a point charge model [8,9,[19][20][21][22] to simulate the ion wake, it has been shown that resonance instability can be triggered when the two coupled wave modes intersect. This phenomenon was recently observed experimentally [18,[23][24][25] in the thermal fluctuation spectrum illustrated by a high-energy-density region at the intersection between the DLWs. This enhanced energy density corresponds to the resonance instability and can result in melting of the plasma crystal at low neutral gas pressures [23][24][25][26].…”
Section: Introductionsupporting
confidence: 68%
“…Using a point charge model [8,9,[19][20][21][22] to simulate the ion wake, it has been shown that resonance instability can be triggered when the two coupled wave modes intersect. This phenomenon was recently observed experimentally [18,[23][24][25] in the thermal fluctuation spectrum illustrated by a high-energy-density region at the intersection between the DLWs. This enhanced energy density corresponds to the resonance instability and can result in melting of the plasma crystal at low neutral gas pressures [23][24][25][26].…”
Section: Introductionsupporting
confidence: 68%
“…However, for the measurements in this experiment, which are an extension of previously reported investigations by Couëdel et al [15], it is necessary to have simultaneous measurements of particles in both the crystalline and melted regions. To accomplish this, a key feature of this experiment is the use of Particle Image Velocimetry (PIV) techniques to make measurements of the particle velocities and to make a clear determination of the transition region between the melted and crystalline zones of the experiment.…”
Section: B Particle Image Velocimetry (Piv) Analysismentioning
confidence: 82%
“…The melting of the two-dimensional plasma crystal was triggered by the mode-coupling instability [13-16, 22, 23]. This instability is driven by the coupling between two branches of the dust-lattice waves, as was predicted theoretically by Ivlev and Morfill [13] and discovered experimentally by Couëdel et al [15]. The instability is typically induced by decreasing the neutral pressure of a gasprovided a rf discharge power is sufficiently low [16]: The reduced pressure ensures low neutral gas friction (i.e., reduced damping of the microparticles), while low dis- Lower panel: Snapshot of a crystal 16.4 s after the beginning of the experiment during the melting phase.…”
Section: A Experimental Setupmentioning
confidence: 99%
“…So phenomenon and mechanisms of an energy transfer between degrees of freedom of a dusty plasma system are of great interest in the field of dusty plasma. One of such mechanisms [6,[18][19][20][21][22] is based on parametric resonance [3-5, 16, 23]. The charged dust particles oscillate in the sheath of the gas discharge.…”
Section: Introductionmentioning
confidence: 99%